By definition of derivative

`f'(x)=lim_(Delta x->0)(f(x+Delta x)-f(x))/(Delta x)`

so for `f(x)=1/(3x-1)` we have

`f'(x)=lim_(Delta x->0)(1/(3x+3Delta x-1)-1/(3x-1))/(Delta x)=lim_(Delta x->0)((3x-1-3x-3Delta x+1)/((3x+3Delta x-1)(3x-1)))/(Delta x)=`

`lim_(Delta x->0)(-3Delta x)/((3x+Delta x-1)(3x-1)Delta x)=lim_(Delta x->0)-3/((3x+3Delta x-1)(3x-1))=`

`-3/(3x-1)^2`

**So your solution is** `f'(x)=-3/(3x-1)^2`

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

By definition of derivative

`f'(x)=lim_(Delta x->0)(f(x+Delta x)-f(x))/(Delta x)`

so for `f(x)=1/(3x-1)` we have

`f'(x)=lim_(Delta x->0)(1/(3x+3Delta x-1)-1/(3x-1))/(Delta x)=lim_(Delta x->0)((3x-1-3x-3Delta x+1)/((3x+3Delta x-1)(3x-1)))/(Delta x)=`

`lim_(Delta x->0)(-3Delta x)/((3x+Delta x-1)(3x-1)Delta x)=lim_(Delta x->0)-3/((3x+3Delta x-1)(3x-1))=`

`-3/(3x-1)^2`

**So your solution is** `f'(x)=-3/(3x-1)^2`